Researching the TCP/IP network with using of modified active queue management REM-algorithm with dynamically split characteristics (DSREM) - Довженко, Тимур Павлович (Technology audit and production reserves, 2016)
This work is devoted to the description of the new method (algorithm) of active queue management (DSREM), developed on the basis of existing REM-method. The object of the research is the system of network router buffer active queue management (AQM), corrected by REM-algorithm. The main disadvantages of this system are the instability of the queue length parameters and the likelihood of marking the router buffer packet, as well as the increase in the percentage of lost and discarded packets with increasing load for data lines in TCP/IP network. The article describes the work of active queue management REM-algorithm. A new, developed by the author and a previously unknown active queue management algorithm with improved quality characteristics (for packet loss and more stable value of the router buffer queue length) based on the REM-algorithm with dynamically split characteristic of control law (DSREM-algorithm). Using TCP/IP-network modeling it is found that DSREM-algorithm in comparison with the REM-algorithm has the best performance for the lost and discarded packets, as well as more stable values of the queue length and the characteristics of the likelihood of marking packets with an increase in the number of incoming message sources. The practical value and scientific novelty of DSREM-method modifying REM-method is to introduce specific parameters (scale factors and stability factor) in the original algorithm, which enhance network performance.